PECULIAR FEATURES OF MACHINING MARKS FORMATION ON SURFACE ОF TITANIUM SPECIMEN WITH SINGLE ELECTRO CONTACT ACTION OF WIRE ELECTRODE-TOOL - M. G. Kiselev; A. V. Drozdov; S. G. Monich; P. S. Bogdan (Наука и техника)
The paper presents an investigation of shape and geometry parameters of machining marks obtained on the surface of titanium specimen with a single electro contact action of a wire electrode-tool. A description of the developed unit and methodology for execution of experimental investigations has been given in the paper. The paper provides and analyzes experimentally obtained data showing the effect of conditions and modes of single electro contact action of wire tool-electrode on the shape and geometrical parameters of machining marks obtained on the surface of titanium specimen. It is shown that the formation of these traces occurs in the context of joint action of both the electrical erosion and mechanical action of the working part of the wire electrode-tool on the surface of the titanium specimen that expands technological capabilities of electro contact treatment while  solving problems associated with targeted modification of the original work-piece surfaces.